Medical emergencies in pediatric blood & marrow transplant and cellular therapies - Agarwal, Nikki; Rotz, Seth; Hanna, Rabi (Frontiers in Pediatrics, 2023)
Hematopoietic stem cell transplant (HCT) is used for many pediatric malignant and non-malignant diseases. However, these patients are at a high risk for emergencies post-transplant, related to prior comorbidities and treatments for the underlying disease, high dose chemotherapy regimen related toxicities, prolonged myelosuppression, and opportunistic infections due to their immunocompromised state. Emergencies can be during preparative regimen and hematopoietic progenitor cell (HPC) infusion, acute post-transplant (pre-engraftment) and late during post engraftment. Infectious complications are the most common cause of morbidity and mortality in the peri-transplant period. Sinusoidal obstructive syndrome is another life-threatening emergency seen in children undergoing HCT, especially in infants. Timely recognition and administration of defibrotide with/without steroids is key to the management of this complication. Another complication seen is transplant associated thrombotic microangiopathy. It can cause multiorgan failure if left untreated and demands urgent identification and management with complement blockade agents such as eculizumab. Cytokine release syndrome and cytokine storm is an important life-threatening complication seen after cellular therapy, and needs emergent intervention with ICU supportive care and tocilizumab. Other complications in acute period include but are not limited to: seizures from busulfan or other chemotherapy agents, PRES (posterior reversible encephalopathy syndrome), diffuse alveolar hemorrhage, idiopathic pulmonary syndrome and allergic reaction to infusion of stem cells. Acute graft versus host disease (GvHD) is a major toxicity of allogeneic HCT, especially with reduced intensity conditioning, that can affect the skin, liver, upper and lower gastrointestinal tract. There has been major development in new biomarkers for early identification and grading of GvHD, which enables application of treatment modalities such as post-transplant cyclophosphamide and JAK/STAT inhibitors to prevent and treat GvHD. Myelosuppression secondary to the chemotherapy increases risk for engraftment syndrome as well as coagulopathies, thus increasing the risk for clotting and bleeding in the pediatric population. The purpose of this article is to review recent literature in these complications seen with pediatric hematopoietic cell transplant (HCT) and cellular therapies and provide a comprehensive summary of the major emergencies seen with HCT.